1997
DOI: 10.1016/s0277-9536(96)00394-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy benefit management, cost-effectiveness analysis and drug formulary decisions

Abstract: Abstract--Pharmacy benefit management companies (PBMs) have evolved over the past decade in response to the increased demand for health care cost containment. Their activities include the implementation of drug formularies and the negotiation of rebates from manufacturers. Our analysis of this industry is based on interviews and materials provided by the top five ranked PBM companies which account for over 80% of beneficiaries covered within formulary plans. The formularies of these companies are relatively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 16 publications
2
48
0
1
Order By: Relevance
“…5 In addition, PBMs often monitor and attempt to alter physicians' prescribing habits among those who disproportionately prohibit generic substitution. Grabowski and Mullins (1997) found that these various incentive measures can save payers 10% or more of their total drug budget.…”
Section: Important Industry Developmentsmentioning
confidence: 99%
“…5 In addition, PBMs often monitor and attempt to alter physicians' prescribing habits among those who disproportionately prohibit generic substitution. Grabowski and Mullins (1997) found that these various incentive measures can save payers 10% or more of their total drug budget.…”
Section: Important Industry Developmentsmentioning
confidence: 99%
“…It can be argued that, under these arrangements wherein the health plan directly contracts with the PBM, there is a moderate probability of aligning financial/clinical incentives across drug/medical services. Recent surveys and case studies reveal that an increasing percentage of HMOs are integrating pharmacy and medical databases (17,32,33).…”
Section: Pbm Services As a Continuummentioning
confidence: 99%
“…FORMULARY AND FORMULARY-RELATED ACTIVITIES Developing, maintaining, and changing formularies are major functions performed by PBMs (10,17,22,43). Formularies provide the overarching structure of the pharmacy benefit because they define which drugs are covered (paid for) by the health plan and thus can be prescribed and dispensed to patients.…”
Section: Pbm Drug Use Control Functionsmentioning
confidence: 99%
See 2 more Smart Citations